Deciphering psychobiotics’ mechanism of action: bacterial extracellular vesicles in the spotlight - Bleibel, Layla; Dziomba, Szymon; Waleron, Krzysztof Franciszek; Kowalczyk, Edward; Karbownik, Michał Seweryn (Frontiers in Microbiology, 2023)
The intake of psychobiotic bacteria appears to be a promising adjunct to neuropsychiatric treatment, and their consumption may even be beneficial for healthy people in terms of mental functioning. The psychobiotics’ mechanism of action is largely outlined by the gut-brain axis; however, it is not fully understood. Based on very recent studies, we provide compelling evidence to suggest a novel understanding of this mechanism: bacterial extracellular vesicles appear to mediate many known effects that psychobiotic bacteria exert on the brain. In this mini-review paper, we characterize the extracellular vesicles derived from psychobiotic bacteria to demonstrate that they can be absorbed from the gastrointestinal tract, penetrate to the brain, carry the intracellular content to exert beneficial multidirectional action. Specifically, by regulating epigenetic factors, extracellular vesicles from psychobiotics appear to enhance expression of neurotrophic molecules, improve serotonergic neurotransmission, and likely supply astrocytes with glycolytic enzymes to favor neuroprotective mechanisms. As a result, some data suggest an antidepressant action of extracellular vesicles that originate even from taxonomically remote psychobiotic bacteria. As such, these extracellular vesicles may be regarded as postbiotics of potentially therapeutic application. The mini-review is enriched with illustrations to better introduce the complex nature of brain signaling mediated by bacterial extracellular vesicles and indicates knowledge gaps that require scientific exploration before further progress is made. In conclusion, bacterial extracellular vesicles appear to represent the missing piece of the puzzle in the mechanism of action of psychobiotics.